High dynamic range photography without a tripod. Issue 2 (2014) - Luigi Barazzetti
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to present a new multi‐image registration methodology that is able to align a set of hand‐held bracketed shots. Design/methodology/approach – The procedure is a two‐step algorithm where corresponding multi‐image points are automatically extracted from the bracketed image sequence and a least squares adjustment recovers transformation parameters. Findings – The images can be processed with high dynamic range algorithms to combine multiple low dynamic range pictures into a single mosaic with a superior radiometric quality. Originality/value – Simulated and real examples are illustrated to prove the effectiveness of the developed affine‐based procedure.